Spillover of domains: testing the influence of work-family conflict on staff at a Southern U.S. prison - Haynes, Stacy H. (Psychology, crime & law, 2025)
Correctional staff are a valuable resource for prisons. Nevertheless, they work in a unique environment characterized by numerous stressors that may affect them at work and at home. The literature on predictors of job stress (both in corrections and in other work environments) is extensive, but few studies have examined the role of work-family conflict. The current study examined how the four types of work-family conflict (i.e., time-, strain-, behavior-, and family-based) affect job stress among staff at a large, state-operated correctional facility in the Southern U.S. While time-, strain-, and behavior-based conflict were positively correlated with job stress at the bivariate level, the influence of time-based conflict on job stress became non-significant after controlling for other demographic and contextual variables. Only strain- and behavior-based conflict remained significant predictors of job stress in the multivariate regression analyses. These findings highlight the importance of differentiating between the various dimensions of work-family conflict. Furthermore, all correctional staff need to be aware of the signs and symptoms of work-family conflict and should be trained in the proper responses and places to refer colleagues when necessary.